Chasing shadows: the untold and deadly story of terrorism in Australia - Campion, Kristy (Allen & Unwin, 2022)
Shadows of empire, 1868-1918 -- 1. The Fenian circle: Irish terrorism -- The revolution generation, 1965-75 -- 2. A socialist utopia: left-wing extremism -- 3. A fascist homeland: the Ustaša -- 4. Quest for state: pro-Palestine terrorism -- Southern Cross terror, 1975-90 -- 5. Spiritual elites: the Ananda Marga -- 6. Promise of vengeance: pro-Armenian terrorism -- 7. Fires in the night : right-wing extremism -- 8. Under sarin skies: Aum Shinrikyo -- Battles cries, 1990 onwards -- 9. White meat: Jemaah Islamiyah -- 10. Caliphate dreaming: the Al-Qaeda franchise -- 11. Civilisation urning: the Islamic State network -- 12. Darkest of hours: the extreme right.